Plants that cure plants as a source for medicines, from pharmaceuticals to herbal remedies - Dauncey, Elizabeth A.; Howes, Melanie-Jayne (Kew Publishing, Royal Botanic Gardens, 2020)
Of the nearly 400,000 plants that have evolved on Earth, around seven percent of them have been used in traditional herbal medicine or as local remedies. More recently, scientific studies have revealed how plants may be sources of important medicines, often in the form of single isolated compounds. Plants That Cure explores these critical compounds and the plants that produce them. This richly illustrated book, filled with color photographs and diagrams, is organized by body system, which feeds into a discussion of the compounds and plants employed for particular conditions, including heart and circulatory problems, fatigue and dementia, nausea and indigestion, respiratory infections, arthritis and joint movement, eye conditions, reproductive issues, and types of cancer. This detailed book examines the mechanisms of action for these plants and also explains how some of their chemical compounds contribute to the functioning and survival of the plants themselves. Essential for herbalists, botanists, and anyone interested in natural remedies and drug discovery, Plants That Cure is the indispensable resource for understanding how medicinal plants work. This work provides an authoritative natural history of the most important medicinal plants, features hundreds of color photos and illustrations, explores the roles of plants in different systems of traditional medicine throughout the world, and looks at specific body systems and the phytochemical compounds used to treat or alleviate systemic conditions, from heart ailments and respiratory infections to reproductive issues.--Source other than the Library of Congress.